SINUSOIDAL NOISE CANCELATION DENGAN MENGGUNAKAN DIGITAL SIGNAL PROCESSING STARTER KIT TMS320C6713 - Yultrisna yultrisna; Andi Syofyan (Elektron : Jurnal Ilmiah, 2012)
Original speech signal is needed both in telecommunications and in some instruments in a variety of fields. Not infrequently, the original audio signal is damaged due to noise. This noise can cause the original signal changes in the actual form. In the final project will be designed FIR filter to remove noise by using TMS320C6713 DSK. Sound signal to be input to the mixed noise removal filter system noise. The mixed voice signal will be searched by subtracting the signal difference to noise signal output FIR filter to get the signal e (n), and then do an adaptation resulting filter coefficients. Results of the adaptive filter coefficients would be put back to calculate the noise signal output next FIR filter. Original voice signal used is the word "sinus" uttered by teenage boys, teenage girls, boys and girls. Girl's voice had the highest frequency with an average 522.50 Hz, the frequency of the sound of the boys 462.63 Hz, the sound frequency of 222.58 Hz girls and voice frequencies teenage boys at 201.49 Hz. Noise signal used is 100 Hz sinusoidal noise. From the test results obtained for the system output signal SNR sound input teenage boy was 19.94 dB. SNR output signal to the input of 21.39 dB girls. SNR signal input output system for boys was 34.70 dB. SNR output signal to the input system daughters of 35.52 dB